Legionella micdadei: A Forgotten Etiology of Growing Cavitary Nodules: A Case Report and Literature Review - Daniel Lachant; Paritosh Prasad (Case Reports in Pulmonology)
Background. Legionella micdadei is a Gram negative bacterium that can stain weakly acid fast. It was first described in 1979 after immunosuppressed patients developed pneumonia at a Pittsburgh VA, initially given the name Pittsburgh Pneumonia Agent. It is the second most common Legionella species causing infection after pneumophila, and typically infects immunocompromised hosts. It is not easy to be cultured which makes diagnosing difficult. Case Presentation. A 31-year-old female with ulcerative colitis, primary sclerosing cholangitis, and cirrhosis presented with fever, chills, shortness of breath, dry cough, and chest pain for five days after being started on immunosuppression for autoimmune hepatitis two months earlier. The first chest CT showed small bilateral cavitary nodules. The nodules continued to grow on subsequent imaging despite what was thought to be appropriate therapy. A transthoracic biopsy was performed which grew Legionella micdadei and the patient improved after being treated with levofloxacin. Conclusion. Legionella micdadei is an atypical pathogen known to cause pneumonia in immunosuppressed patients. This case highlights a typical presentation of an atypical infection not commonly thought about and should be considered when nodules are growing despite being on broad antimicrobial therapy.